Sequence-Specific Electrochemical Genosensor for Rapid Detection of blaOXA-51-like Gene in Acinetobacter baumannii - Swarnaletchumi Kanapathy; Godwin Attah Obande; Candy Chuah; Rafidah Hanim Shueb; Chan Yean Yean; Kirnpal Kaur Banga Singh (Microorganisms, 2022)
Acinetobacter baumannii (A. baumannii) are phenotypically indistinguishable from the Acinetobacter calcoaceticus–A. baumannii (ACB) complex members using routine laboratory methods. Early diagnosis plays an important role in controlling A. baumannii infections and this could be assisted by the development of a rapid, yet sensitive diagnostic test. In this study, we developed an enzyme-based electrochemical genosensor for asymmetric PCR (aPCR) amplicon detection of the blaOXA-51-like gene in A. baumannii. A. baumanniiblaOXA-51-like gene PCR primers were designed, having the reverse primer modified at the 5′ end with FAM. A blaOXA-51-like gene sequence-specific biotin labelled capture probe was designed and immobilized using a synthetic oligomer (FAM-labelled) deposited on the working electrode of a streptavidin-modified, screen-printed carbon electrode (SPCE). The zot gene was used as an internal control with biotin and FAM labelled as forward and reverse primers, respectively. The blaOXA-51-like gene was amplified using asymmetric PCR (aPCR) to generate single-stranded amplicons that were detected using the designed SPCE. The amperometric current response was detected with a peroxidase-conjugated, anti-fluorescein antibody. The assay was tested using reference and clinical A. baumannii strains and other nosocomial bacteria. The analytical sensitivity of the assay at the genomic level and bacterial cell level was 0.5 pg/mL (1.443 µA) and 103 CFU/mL, respectively. The assay was 100% specific and sensitive for A. baumannii. Based on accelerated stability performance, the developed genosensor was stable for 1.6 years when stored at 4 °C and up to 28 days at >25 °C. The developed electrochemical genosensor is specific and sensitive and could be useful for rapid, accurate diagnosis of A. baumannii infections even in temperate regions.